ANALISIS KONSEP HERMENEUTIKA HADIS PERSPEKTIF MUHAMMAD ARKOUN - Andris Nurita; Masruhan Masruhan (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2021)
The formation of hadith text is a response to the existence of past realities, both micro and macro, so that the language contained in the text follows the context at the time of the formation of the text. The development of language and dynamics of life is increasingly significant, of course the text is not able to reach comprehensively when only based on textualist and dogmatic understanding. Because, the events behind the formation of the text are different from the reality that occurs at this time. Therefore, it takes a method that can break the freeze of the text to gain comprehensive and contextual meaning to the demands of the times. In this study, using qualitative method to analyze in the form of verbal narrative based on data facts that are rationalizm. Muhammad Arkoun as a neo-modernist thinker tried to interpret the concept of hermeneutics as a solution in solving the freeze of the text. The hermeneutic mindset of Arkoun focuses on philosophy as a dynamic thinking tool that is not limited to space and time. According to him, hermeneutics are inseparable from applied Islamology, semiotics and historical socio- The study of a diachronic and synchronic language becomes the main state of studying a text, resulting in a comprehensive thinking with critical reason based on phenomenological analysis.